2021
DOI: 10.1109/tbcas.2021.3115178
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Positive Activity Recognition - From Kinetic Energy Harvesting to Smart Self-Sustainable Wearable Devices

Abstract: Wearable, intelligent, and unobtrusive sensor nodes that monitor the human body and the surrounding environment have the potential to create valuable data for preventive human-centric ubiquitous healthcare. To attain this vision of unobtrusiveness, the smart devices have to gather and analyze data over long periods of time without the need for battery recharging or replacement. This article presents a software-configurable kinetic energy harvesting and power management circuit that enables selfsustainable wear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…It is commonly utilized in energy harvesting applications such as EH, solar chargers, thermal electric generators (TEG), wireless sensor networks (WSN), and portable and wearable health devices. The TI BQ25570 chip is readily available in the market, and its features have been extensively discussed in numerous papers [14][15][16].…”
Section: Cold-startmentioning
confidence: 99%
“…It is commonly utilized in energy harvesting applications such as EH, solar chargers, thermal electric generators (TEG), wireless sensor networks (WSN), and portable and wearable health devices. The TI BQ25570 chip is readily available in the market, and its features have been extensively discussed in numerous papers [14][15][16].…”
Section: Cold-startmentioning
confidence: 99%
“…Recently, Alessandrini et al, presented a recurrent neural network (RNN), deployed on an embedded device, which takes in input data from Photoplethysmography (PPG) and tri-axial accelerometer sensors to infer the current human activity [ 30 ]. Similarly, Coelho et al [ 17 ] and Mayer et al [ 31 ] showed the adequacy of different deep learning models to be run on low-power platforms. Although the HAR on top of low-power devices is the common thread of these recent works, in none of the cases do authors analyze trade-offs between network complexity and resources utilization nor the impact on inference time or on measured energy consumption in real conditions.…”
Section: Related Workmentioning
confidence: 99%
“…Matching is particularly crucial for small-sized harvesters with an output power of a view microwatts that need to supply wireless sensor nodes with peak power of milliwatts. Finally, there is not only the requirement to study and optimize the circuitry itself but also to precisely analyze the application-specific energy statistics to ensure long-term reliability [23]. A resilient power path design capable of overcoming temporary absences of environmental power, e.g., with cold start circuitry, allows to partially circumvent this critical design point but does not ensure continuous availability [24].…”
Section: Related Workmentioning
confidence: 99%